Cognitive Abilities, Student Character, and Teacher Self-Evaluation Competencies Through Character Education Programs - Marhadi, Hendri (Jurnal Pendidikan Indonesia, 2024)
Many students show a gap between academic achievement and character development, such as discipline, responsibility, and empathy. This reflects the suboptimal integration of character values ​​into the learning process. This study aimed to investigate the effectiveness of character education programs on academic competence, student character, and teacher competence. The research method was a quasi-experiment to see the effectiveness of character education programs implemented in elementary schools. The sample of this study was 500 students and 300 teachers from 10 elementary schools. The research instruments used were questionnaires, rubrics and other supporting data. The data analysis used was ANCOVA, MANOVA, and MANCOVA analysis. The research findings showed that character education improved cognitive abilities, developed positive student character, and improved teacher competence through self-evaluation. The increase in mental ability was seen in students' reading ability. The positive character improvements were social interaction skills, discipline, empathy, and perceptions of the school environment. The increase in competence seen in teachers after receiving intervention was an increase in self-evaluation skills that could improve the quality of teaching, such as motivation, enjoyment of teaching, interaction skills, stakeholder support, parental support, co-worker support, and trust in students. This study has implications that character education can be used as an alternative intervention to develop academic, non-academic and teacher competency.